2020
DOI: 10.5194/bg-2020-409
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantifying the Importance of Antecedent Fuel-Related Vegetation Properties for Burnt Area using Random Forests

Abstract: Abstract. The seasonal and longer-term dynamics of fuel accumulation affect fire seasonality and the occurrence of extreme wildfires. Failure to account for their influence may help to explain why state-of-the-art fire models do not simulate the length and timing of the fire season or interannual variability in burnt area well. We investigated the impact of accounting for different timescales of fuel production and accumulation on burnt area using a suite of random forest regression models that included the im… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
(73 reference statements)
0
2
0
Order By: Relevance
“…They do not require physical parameterization [19], which is particularly beneficial when the number of considered variables is extensive. Random forest (RF) ML models are highly suitable for investigating emergent fire relationships, mainly because of their ability to evaluate non-linear relationships [7,[20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…They do not require physical parameterization [19], which is particularly beneficial when the number of considered variables is extensive. Random forest (RF) ML models are highly suitable for investigating emergent fire relationships, mainly because of their ability to evaluate non-linear relationships [7,[20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of present-day fire relationships using satellite-derived data have shown that vegetation properties determining fuel availability are the strongest determinants of fire occurrence (Bistinas et al, 2014;Forkel et al, 2019aForkel et al, , 2019bKuhn-Régnier et al, 2020). This suggests that palaeo-vegetation data could provide a way of reconstructing burnt area in the past, particularly at times when human influences on land cover were less important.…”
Section: Introductionmentioning
confidence: 99%